The criminal and administrative type of front running practice and damage to the securities market - Lins, Luís Henrique (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
The purpose of this article is to clarify non-equitable market practices and crimes against the securities market, especially the practice of front running, in addition to point cases in which individuals acted illegally and indicate the damages to the market that this practice has caused. It also explains the possible criminal and administrative sanctions applied to the practice of front running presently in Brazilian law and whether using HTFs is considered a way of front running. The conclusion is that the practice of front running affects the proper functioning of the securities market. It damages the liquidity of assets and the parity of information principle through the inappropriate use of inside information. In addition, there is an appeal for hardening custodial sentences on crimes against the securities market, as it has greater coercive power than regular fines.